Radiotherapy for Recurrent Keloid: A Case Report - Christina Hari Nawangsih Prihharsanti; Muhamad Rizqi Setyarto; Dion Firli Bramantyo (Faculty of Medicine, Diponegoro University, 2020)
Background: Keloid is a benign growth of connective tissue. There are several risk factors that play a role in keloid growth. Excision surgery is one of the modalities in the treatment of keloids. However, excision surgery alone has a recurrence rate of 45-100%.Case: Male, 37 years old, with complaints arising from a keloid lesions in the left earlobe since three years ago with a history of previous injuries. The lesions is then operated on but always grows back postoperatively. The number of surgeries that have been carried out three times with further treatment in the form of corticosteroid injection. However, keloid still recurrence. Finally it was decided to undergo treatment with surgery followed by radiotherapy within a period of no more than 24 hours postoperatively. Follow-up after six months gave good results without recurrence.Discussion: Keloid has a high recurrence rate after excision surgery. Surgery followed by radiotherapy has a low recurrence rate compared to surgery or surgery followed by administration of corticosteroid injections. Radiotherapy as adjuvant therapy for postoperative keloid excision has the role of sterilizing the connective tissue stem cell active fibroblasts and acute inflammatory cells that grow in the early postoperative period. A study states that administration of postoperative radiation with electrons in keloids in the earlobe at a dose of 15 Gy in three fractions gives a low recurrence rate and a low risk of side effects in the surrounding soft tissue.